(untitled) (African Journal of Biomedical Research, 2023)
Sulfadoxine-pyrimethamine (SP) is no longer recommended for the treatment of uncomplicated falciparum malaria due to its increasing failure rate, but is still being used as preventive treatment during pregnancy and in chemoprevention. SP targets either dihydrofolatereductase, dhfr and dihydroptereoate synthase, dhps involved in folate biosynthesis in the parasite. This study screened for mutation in SP target genes, dhfr and dhps in Plasmodium falciparum among out-patients in Awka South, Anambra State. Blood samples were obtained from 210 patients aged 5-64 years with febrile conditions. The blood samples were screened for malaria parasites using blood smear stained with giemsa. The dhfr and dhps genes were amplified using PCR and sequenced using dideoxy chain termination method. The overall prevalence of Plasmodium falciparum malaria in this study was 74.8 % (157/210) out of which 19.1 % (30/157) had high parasite count of ≥ 4000 asexual parasite /µL of blood. Out of this number, 14.6% [23/157] with high yield and purity of ≥50 ng/µL and ≥1.7 respectively were considered good for downstream PCR.The result showed that dhfr alone was detected in 8/23 [34%], dhps alone was seen in 7/23 [30%] while both dhfr and dhps genes were seen in 4/30 [13%]. In all [8/23] parasites where dhfr was detected, mutations at Asn-108, Ile-51 and Arg-59 were present. Additional mutation was seen in 75% [6/8] at position Leu-164. Gly-581, Phe-436 and Thr-613 mutations were seen in all isolates where dhps were detected. Rare Leu-164 and Thr-613 mutants were seen in dhfr and dhps respectively. These mutants may be responsible for SP resistance in this region, suggesting an increased compromise over the efficacy of SP in malaria treatment.